Analisis Pengaruh Perubahan Dimensi Kincir Air Terhadap Kecepatan Aliran Air (Studi Kasus: Desa Pandan Enim) - Oggy Sukasah Henry; Arifin Daud; Helmi Haki (Jurnal Teknik Sipil dan Lingkungan, 2013)
Muara Enim is one of the districts in southern Sumatra. To support the rapid advancement of agriculture in the region is necessary a good irrigation. location field in the village of pandan enim higher than the water source, therefore the need for assistance to waterwheel water into irrigation canals. There should also be planning dimensions to accommodate irrigation water resulting from rain water wheel and the corresponding calculation. Paddy fields in the village of pandan enim enim estuary district has a land area of ​​1500 hectares is rain-fed types. With the help of the water wheel in the dry season so that people's needs can also be met on the agricultural aspects. Keywords : water wheel, water flow,velocity of water flow